Modes of Death in a Pediatric Cardiac ICU*. Issue 5 (May 2016) - Polito, Angelo; Garisto, Cristiana; Pezzella, Chiara; Iacoella, Claudia; Cogo, Paola E.
Abstract : Objective: To determine epidemiology and proximate causes of death in a pediatric cardiac ICU in Southern Europe. Design: Retrospective chart review. Setting: Single-center institution. Patients: We concurrently identified 57 consecutive patients who died prior to discharge from the cardiac ICU. Interventions: None. Measurements and Main Results: Over the study period, there were 57 deaths for a combined mortality rate of 2.4%. Four patients (7%) were declared brain dead, 25 patients (43.8%) died after a failed resuscitation attempt, and 28 patients (49.1%) died after withholding or withdrawal of life-sustaining treatment. Cardiorespiratory failure was the most frequent proximate cause of death (39, 68.4%) followed by brain injury (14, 24.6%) and septic shock (4, 7%). Older age at admission, presence of mechanical ventilation and/or device-dependent nutrition support, patients on a left-ventricular assist device and longer cardiac ICU stay were more likely to have life support withheld or withdrawn. Conclusions: Almost half of the deaths in the cardiac ICU are predictable, and they are anticipated by the decision to limit life-sustaining treatments. Brain injuries play a direct role in the death of 25% of patients who die in the cardiac ICU. Patients with left-ventricular assist device are associated with withdrawal of treatment.